2010
DOI: 10.1007/s10758-010-9165-7
|View full text |Cite
|
Sign up to set email alerts
|

Role of Interaction in Enhancing the Epistemic Utility of 3D Mathematical Visualizations

Abstract: Many epistemic activities, such as spatial reasoning, sense-making, problem solving, and learning, are information-based. In the context of epistemic activities involving mathematical information, learners often use interactive 3D mathematical visualizations (MVs). However, performing such activities is not always easy. Although it is generally accepted that making these visualizations interactive can improve their utility, it is still not clear what role interaction plays in such activities. Interacting with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…They also indicated that it was not easy to interact with the touchpad while also carrying out motion gestures with the device. This seemed to agree with earlier research about input devices, where it was found that despite providing multiple features that were considered useful, actual users may not be able to take advantage of them and use more than one feature simultaneously [18,46].…”
Section: Resultssupporting
confidence: 91%
“…They also indicated that it was not easy to interact with the touchpad while also carrying out motion gestures with the device. This seemed to agree with earlier research about input devices, where it was found that despite providing multiple features that were considered useful, actual users may not be able to take advantage of them and use more than one feature simultaneously [18,46].…”
Section: Resultssupporting
confidence: 91%
“…As a visualization tool, no direct or explicit instructions about how they should interact with the tool are provided. Users have to explore and analyze by themselves using the tool's visual interactive functions and interpret the results and draw their own conclusions [76,77]. Figure 1 shows the interface of the tool, which is implicitly divided into 5 sections: (1) Synchronize function: The transformation of three solids will be synchronous when changing from one same shape to another same shape; (2) User ID: It indicates how many users are using the tool at the same time; (3) 3D solid visualizations: There are three solids, cube, tetrahedron and Octahedron; (4) Solid transition maps (STM): They can support active navigation within and between visualizations.…”
Section: Visualization Application Overviewmentioning
confidence: 99%
“…If interactions do not contribute in any significant manner to the exploration process, instead of being beneficial, they may actually lead to unwanted consequences-sometimes referred to as "interaction costs" [59]. Some of these consequences include: spending time finding an appropriate interaction, figuring out what combinations of interactions to use, and spending time to try them out [60]. This is also in line with research in the personalization of user interfaces for productivity applications, where task performance was found to be faster for a minimalist interface than for an interface with a fuller set of choices [61].…”
Section: Discussionmentioning
confidence: 99%